Progressive Supranuclear Palsy - Golbe, Lawrence I. (Seminars in Neurology, 2014)
Progressive supranuclear palsy is a disorder of tau protein aggregation. Its clinical spectrum is now known to be wider than originally described, with a phenotype resembling Parkinson disease accounting for a third of cases. However, at least half of the patients with PSP exhibit the classic bradykinesia with disproportionate postural instability, erect posture with nuchal rigidity, frontal behavioral and cognitive changes, vertical gaze palsy, and other disabling brainstem deficits. Nonmendelian genetic risk factors exist, but PSP is almost entirely sporadic, with a prevalence of five to six persons per 100,000, mean onset age of 63, and median survival of 7 years. Clinical diagnostic criteria with excellent specificity and a clinical rating scale sensitive to progression are available. Diagnosis remains clinical, although magnetic resonance imaging and cerebrospinal fluid measures are showing promise as early-stage screening tools. Multiple candidate neuroprotective medications have proven ineffective to date. Treatment remains supportive, although coenzyme Q-10 has shown preliminary symptomatic efficacy and levodopa may provide transient, modest benefit.
Keywords: progressive supranuclear palsy; brainstem; tau; parkinsonism; frontal dementia